Risk Factors of Kidney Failure Patients in Sardjito Hospital Yogyakarta - Dewi Yuniasih; Novi Wijayanti Sukirto; Barkah Djaka Purwanto (Universitas Ahmad Dahlan, 2020)
The purpose of this study is to identify patients at high risk of kidney failure in order to plan treatment. Cross-sectional research method, carried out at the CAPD Outpatient Installation of Dr. Sardjito General Hospital, from October 2018 to November 2018. The results showed three major risk factors for kidney failure, namely hypertension (49.1%), diabetes (17.5%) %) and nephrotoxic (15.8%). The conclusion from the study is hypertension is the highest risk factor for kidney failure.